The use of stated preference and choice models in the analysis of tourists’ preferences: the Minho-Lima sub-region (Portugal) case - Vareiro, Laurentina (2007)
Some territories use its natural, historical and ethnographical resources aiming to preserve resources and to increase revenue and employment. In order to efficiently promote the folder of products and services available and attracting tourists, decision makers, private and public, need to know and incorporate in its marketing strategies tourists’ preferences. In this paper we illustrate the use of stated preferences as an instrument to identify national and foreign tourists’ preferences in what concerns the products and services the Minho-Lima sub-region (Portugal) touristic destination should offer. As a starting point, we have taken the three general groups of touristic resources mentioned above as attributes. We believe the previously identified methodology can be a valuable instrument in the identification of strengths and weaknesses of the selected territory and, thus, giving support to the decision making process behind its future tourist development and external promotion.